Reliability of ChatGPT answers to common questions on developmental dysplasia of the hip as an information source for parents - Vertesich, Klemens; Ortmayr, Joachim; Windhager, Reinhard; Willegger, Madeleine (Frontiers in Pediatrics, 2025)
BackgroundArtificial intelligence (AI), particularly AI-based large language models (LLM) like ChatGPT, is increasingly shaping how information is accessed, offering patients a new source for understanding complex medical conditions. Given the physical, emotional, and logistical challenges that parents are faced when their baby is diagnosed with developmental dysplasia of the hip (DDH), the demand for clear and accessible educational resources is high. This study aimed to evaluate the quality and reliability of ChatGPT's responses to frequently asked questions about DDH.MethodsThis study assessed the quality of responses generated by the AI chatbot ChatGPT 4o to eight frequently asked questions about DDH, derived from real consultations in a pediatric orthopedic clinic Responses were generated during one interaction per question using a ChatGPT account not previously exposed to medical information. Responses were evaluated by two individual readers using a standardized rating system, comparing them to current literature, patient education resources, and consensus guidelines. Each response was categorized by its level of informational accuracy and completeness, and descriptive statistics were calculated to quantify performance.ResultsChatGPT 4o was able to generate structured responses to all eight parental questions. The responses were rated in 12.5% excellent, 25.0% satisfactory with minimal clarification, 50.0% satisfactory with moderate clarification, and 12.5% unsatisfactory due to missing or inaccurate information.ConclusionChatGPT provided satisfactory answers to questions about DDH and may serve as a useful supplementary information resource for parents. However, due to limitations in presenting detailed diagnostic and treatment pathways, it should be viewed as an adjunct to, not a replacement for, specialist medical consultation.